Correction: The expression of the surfactant proteins SP-A and SP-B during postnatal alveolarization of the rat lung. - Franziska Roeder; Lars Knudsen; Andreas Schmiedl (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297889.].